Post-mating shift towards longer-chain cuticular hydrocarbons drastically reduces female attractiveness to males in a digger wasp. (July 2017) - Polidori, Carlo; Giordani, Irene; Wurdack, Mareike; Tormos, José; Asís, Josep D.; Schmitt, Thomas
Graphical abstract: Highlights: In a digger wasp, female attractiveness to males shortly drops after mating. Change in male behavior was associated with a change in female CHC profile. Many short-length alkanes are exclusive or more abundant in virgin females. A rapid detection of virgin females is essential due to strong male competition. This pattern is found for the first time in digger wasps, the basal group to bees. Abstract: Females of most aculeate Hymenoptera mate only once and males are therefore under a strong competitive pressure which is expected to favour the evolution of rapid detection of virgin females. In several bee species, the cuticular hydrocarbon (CHC) profile exhibited by virgin females elicits male copulation attempts. However, it is still unknown how widespread this type of sexual communication is within Aculeata. Here, we investigated the use of CHCs as mating cues in the digger wasp Stizus continuus, which belongs to the family (Crabronidae) from within bees arose. In field experiments, unmanipulated, recently emerged virgin female dummies promptly elicit male copulation attempts, whereas 1–4 days old mated females dummies were still attractive but to a much lesser extent. In contrast, old (10–15 days) mated female dummies did not attract males at all. After hexane-washing, attractiveness almost disappeared but could be achieved by adding CHC extracts from virgin females even on hexane-washed old mated females. Thus, the chemical base of recognition of females as appropriate mating partner by males is coded in their CHC profile. Accordingly, differences in CHC profiles can be detected between sexes, with males having larger amounts of alkenes and exclusive long-chain alkanes, and within females specially according to their mating status. Shortly after mating, almost all of the major hydrocarbons found on the cuticle of females undergo significant changes in their abundance, with a clear shift from short-chain to long-chain linear and methyl-branched alkanes. The timely detection of virgin females by males in S. continuus could be advantageous within the narrow period of female emergence, when male-male competition is strongest.